Preparation method of high-temperature excitation coil based on AMB process
Through the preparation method based on the AMB process, silicon nitride ceramic and brazing solder paste are combined with metal foil at high temperatures, the problem of insufficient performance of the excitation winding insulation layer is solved, and high reliability and long service life are achieved in high temperature environments.
Patent Information
- Application Number
- CN202411861239.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When the existing magnetic levitation bearing system is used in high temperature environments, the insulation layer performance of the excitation winding is insufficient, resulting in short circuits in coils and oxidation of metal conductors, reducing the reliability and service life of the system.
Using a preparation method based on the AMB process, silicon nitride ceramic is used as the insulating layer, and metal foil is bonded with ceramic at high temperature through brazing paste to form a tight bonding layer to improve the thermal shock resistance and thermal stability of the coil.
In a high temperature environment of 550°C to 600°C, the reliability and service life of the excitation coil are improved, and the insulating layer damage and coil short circuit are avoided.
Smart Images

Figure CN119446774A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic suspension, and in particular to a method for preparing a high-temperature excitation coil based on an AMB process. Background Art
[0002] Compared with traditional mechanical bearing systems, magnetic bearing systems have the advantages of lighter weight, smaller vibration, and simpler structure. As the fields of magnetic bearing promotion become wider and wider, the performance requirements for magnetic bearings are also getting higher and higher. For example, the application in aviation multi-electric engines and gas turbines requires magnetic bearings to maintain long-term stable operation in high temperature environments above 550°C. The mechanical system of ordinary magnetic bearings can only work below 180°C due to the performance of the insulation layer of the excitation winding. It uses ordinary insulating varnish as the insulating layer. This insulating varnish will undergo rapid oxidation and combustion in a temperature environment above 200°C and be destroyed, resulting in the coil short-circuiting and metal wire oxidation due to insulation failure, thereby reducing the reliability and service life of the magnetic bearing system. At present, foreign countries mostly use ceramic coating as the insulating layer of metal wires, which can work for a long time below 1000℃, but the ceramic layer is brittle and easy to break during coil winding and use, causing short circuit between metal wires; China mostly uses two types of insulation layers: glass fiber and multi-layer insulation layers. Glass fiber is simple to wind as an insulation layer but is prone to aging at high temperatures, and the increase in the wire diameter of the multi-layer insulation layer causes the volume of the excitation coil to increase.
[0003] AMB (Active Metal Brazing) can wet and react the interface between metal and ceramic at a high temperature of about 800℃ to 1200℃ using solder containing active elements such as Ti and Zr, thereby achieving heterogeneous bonding between ceramic and metal. Because it achieves the bonding of ceramic and metal through chemical reaction at high temperature, its bonding strength is higher and its reliability is better. In addition, silicon nitride ceramics not only have high insulation, high dielectric constant and low dielectric loss, but also have excellent comprehensive thermodynamic properties such as high strength, high toughness, high temperature resistance and high reliability. Therefore, the high-temperature excitation coil prepared by the AMB process using silicon nitride ceramics as the insulating layer will have higher reliability than the traditional wound excitation coil.
[0004] In summary, in order to solve the above problems, it is of great significance to prepare a high-temperature excitation coil based on the AMB process. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a high-temperature excitation coil based on the AMB process to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a high-temperature excitation coil based on an AMB process comprises the following steps:
[0008] S1: opening holes in silicon nitride ceramics: opening through holes and positioning holes on the silicon nitride ceramic sheet, cleaning and drying, and obtaining a pre-opened silicon nitride ceramic sheet;
[0009] S2: Through-hole filling and surface screen printing: Fill the through-holes pre-opened by the pre-opened silicon nitride ceramic sheet with solder paste, and screen print a layer of solder paste on the upper and lower surfaces of the pre-opened silicon nitride ceramic sheet, and bake to obtain a pre-coated silicon nitride ceramic sheet with solder paste;
[0010] S3: Vacuum sintering of metal foil and silicon nitride ceramic: stack a piece of metal foil on the upper and lower surfaces of the silicon nitride ceramic sheet pre-coated with brazing paste, and perform high-temperature vacuum brazing to obtain a metal foil-coated silicon nitride ceramic motherboard;
[0011] S4: Coil patterning and surface treatment: laminating, exposing, developing, etching, stripping and drying the upper and lower surfaces of the metal foil-covered silicon nitride ceramic motherboard to obtain a patterned silicon nitride ceramic motherboard covered with metal coils, and then coating the metal coil surfaces on the upper and lower surfaces with an anti-oxidation metal layer to obtain a motherboard A;
[0012] S5: Preparation of a single-layer silicon nitride ceramic metal coil: cutting the motherboard A prepared in step S4 into small pieces according to the designed size by laser, and removing the non-coil area in the middle of the small piece to obtain a single-layer silicon nitride ceramic metal coil;
[0013] S6: Preparation of ceramic separator: marking and punching the ceramic separator according to the outer dimensions of the single-layer silicon nitride ceramic metal coil and the non-coil area, and opening holes at corresponding positions of the through holes of the single-layer silicon nitride ceramic metal coil to form conductive holes, thereby obtaining a ceramic separator;
[0014] S7: Lamination and vacuum sintering: Assemble the single-layer silicon nitride ceramic metal coil and the ceramic separator from bottom to top, and sinter them under pressure to obtain a high-temperature excitation coil.
[0015] Preferably, in step S1, the thickness of the silicon nitride ceramic sheet is 0.2-0.4 mm, and the surface roughness of the ceramic is Ra 0.2-0.6 μm; the aperture of the through hole is 0.2-0.8 mm; and the aperture of the positioning hole is 1-5 mm.
[0016] Among them, the through holes are used to fill metal slurry to make the double-sided silicon nitride ceramic conductive, and the positioning holes are used as alignment holes for subsequent circuit exposure and ceramic sheet cutting.
[0017] Preferably, in step S2, the screen-printed thickness of the solder paste is 8-15 μm; the solder paste comprises the following substances, calculated by mass percentage: 8-12% organic carrier, 3-8% active metal powder, and the rest is metal powder.
[0018] Preferably, the organic carrier includes the following substances, in parts by mass: 7.5-8.5 parts of ethyl cellulose, 3-4 parts of hydrogenated castor oil, 1.5-2.5 parts of dioctyl phthalate, 3-4 parts of dibutyl phthalate, 74-76 parts of terpineol, 3.5-4.5 parts of defoamer GP330, and 3.5-4.5 parts of coupling agent KH550.
[0019] Preferably, the metal powder comprises silver, copper, nickel and tin in a mass ratio of 60-70:20-30:0-5:0-10; the metal powder is a spherical powder with a particle size of 0.2-1 μm; and the active metal comprises one or both of titanium and zirconium.
[0020] Preferably, in step S3, the metal foil includes one of silver foil, copper foil and nickel foil, and has a thickness of 0.1 to 0.5 mm.
[0021] Preferably, in step S4, the wire width in the metal coil is 0.5-3 mm, and the spacing is 0.6-1 mm; the metal in the anti-oxidation metal layer includes one of silver and gold, and the thickness is 0.5-1 μm.
[0022] Preferably, the ceramic sheet is a silicon nitride ceramic sheet with a thickness of 0.1 to 0.4 mm.
[0023] Preferably, during the stacking assembly process, the stacking method is to stack the ceramic sheets and the single-layer silicon nitride ceramic metal coils in an alternating manner from bottom to top, with the ceramic sheets being the top.
[0024] Preferably, the single-layer silicon nitride ceramic metal coil needs to be pre-screened with a layer of solder paste on the upper and lower surfaces of the inner connecting ring and the upper and lower surfaces of the outer connecting ring and then dried, and the solder paste is consistent with that used in step S2; the ceramic separator needs to be pre-filled with copper particles at the via hole; the thickness of the copper particles is twice the sum of the thickness of the metal foil and the thickness of the ceramic separator; the length and width of the copper particles are both 0.5 to 3 μm smaller than the size of the via hole; before the copper particles are filled, their outer surface needs to be wrapped with a layer of solder paste so that the copper particles can be fixed at the via hole.
[0025] More preferably, in step S2, during the drying process, the temperature is 95-105°C, and the time is 10-15 min; in step S3, during the high-temperature vacuum brazing process, the temperature is 850-950°C, the time is 0.5-1 h, and the vacuum degree is 0.01 Pa; in step S7, during the pressure sintering process, the temperature is 850-950°C, the time is 0.5-1 h, and the pressure is 0.01-0.1 MPa.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The combination of the metal coil and silicon nitride ceramic and the combination of the ceramic separator and the coil ceramic in the present invention are both based on the AMB process. The active metal contained in the silk-screen solder paste can wet the surface of silicon nitride ceramic at high temperature, so that the metal foil and the surface of silicon nitride ceramic react chemically, so that the two are very tightly combined; and because the sintering temperature is high, the bonding layer between the metal coil and the silicon nitride ceramic can still maintain a high bonding strength at 550℃~600℃, so the thermal shock resistance and thermal stability of the entire multi-layer coil are good. Compared with the existing excitation coil with ceramic coating or glass fiber as the insulating layer, the excitation coil of the present invention uses silicon nitride ceramic as the insulating layer, and the metal coil is brazed and fixed to the surface of silicon nitride ceramic to form a coil layer. Silicon nitride ceramic has good thermal shock resistance, and the insulating layer is difficult to be damaged, and the reliability is high. The present invention also adopts the interleaved ceramic separator and coil layer prepared by silicon nitride ceramic to stack and assemble, so that even if the silicon nitride ceramic insulating layer cracks, the metal coils will not directly contact each other to cause the coil to short-circuit, thereby enhancing the reliability of the excitation coil as a whole. Therefore, the excitation coil prepared based on the AMB process of the present invention has higher reliability and service life in an environment of 550° C. to 600° C.
[0028] (2) The present invention uses solder paste to fix the metal foil on the pre-opened ceramic surface by high-temperature brazing, and performs a series of etching operations on the metal foil, thereby obtaining a patterned silicon nitride ceramic motherboard covered with a metal coil. This can make the thickness and spacing of the wires uniform, which helps to generate a uniform magnetic field and improve the reliability of the excitation coil; and the surface is silvered or gold-plated to make the metal wire less likely to oxidize at high temperatures, further improving the reliability of the coil; at the same time, the present invention removes the openings in the non-coil area in the middle of the ceramic, thereby reducing the weight of the single-layer silicon nitride ceramic metal coil and facilitating the penetration of the magnetic wire generated by the excitation coil.
[0029] (3) In the excitation coil prepared by the present invention, the metal coils on the upper and lower sides of the single-layer silicon nitride ceramic are connected to each other through the internal through holes, and the metal coils on the upper and lower sides of the silicon nitride ceramic are connected to each other through the copper particles filled in the through holes reserved by the ceramic separator. Through these two types of conduction, the coils form continuous conduction between the first layer and the last layer, and the through hole size is small, which can be used for batch production by silk screen filling without affecting the strength of the ceramic. At the same time, the length and width of the copper particles filled in the through holes reserved by the present invention are slightly smaller than the size of the through holes, and the thickness is the sum of the thickness of the upper and lower coil layers plus the thickness of the ceramic separator, and a layer of solder paste is wrapped on the surface of the copper particles. This can ensure that they can be in close contact with the copper foil of the upper and lower coil layers of the ceramic separator after sintering, and can reduce local poor contact or difficulty in assembly due to the size difference of the copper particles, thereby increasing the reliability of the excitation coil. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a process flow chart of the present invention;
[0031] Figure 2 This is a schematic diagram of a single silicon nitride ceramic pre-opened hole of the present invention;
[0032] Figure 3 It is a schematic diagram of a single silicon nitride ceramic covered with a metal coil according to the present invention;
[0033] Figure 4 Schematic diagram of a single ceramic separator of the present invention;
[0034] Figure 5 is a schematic diagram of a two-layer silicon nitride ceramic metal coil of the present invention;
[0035] Figure 6 This is a schematic diagram of the resistance measurement of the sample prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0037] It should be noted that there is no special restriction on the purchase manufacturers of all raw materials involved in the present invention, and exemplary examples include: ethyl cellulose, hydrogenated castor oil, dioctyl phthalate, dibutyl phthalate, terpineol, defoamer GP330, coupling agent KH550 are all commercially available.
[0038] Among them, in the following embodiments, parts are parts by mass; the solder paste includes the following substances, calculated by mass percentage: 10% organic carrier, 5% active metal powder, and the rest is metal powder; the organic carrier includes the following substances, calculated by mass percentage: 8 parts of ethyl cellulose, 3.5 parts of hydrogenated castor oil, 2 parts of dioctyl phthalate, 3.5 parts of dibutyl phthalate, 75 parts of pine alcohol, 4 parts of defoamer GP330, and 4 parts of coupling agent KH550; the metal powder includes silver, copper, nickel, and tin in a mass ratio of 65:25:2.5:5; the metal powder is a spherical powder with a particle size of 0.2 to 1 μm; the active metal is titanium.
[0039] Embodiment 1: A method for preparing a high temperature excitation coil based on the AMB process, comprising the following steps:
[0040] S1: Opening holes in silicon nitride ceramics: Use laser cutting equipment to open holes in silicon nitride ceramics. Figure 2 The through holes (aperture of 0.3 mm) and positioning holes shown are cleaned and dried to obtain a pre-opened silicon nitride ceramic sheet;
[0041] S2: Through-hole filling and surface screen printing: Fill the through-holes pre-opened by the pre-opened silicon nitride ceramic sheet with solder paste, and screen print a layer of solder paste on the upper and lower surfaces of the pre-opened silicon nitride ceramic sheet, transfer it to an oven and bake it at 100°C for 12 minutes to obtain a pre-coated silicon nitride ceramic sheet with solder paste;
[0042] S3: Vacuum sintering of metal foil and silicon nitride ceramic: A 0.3 mm thick copper foil is stacked on the upper and lower surfaces of the pre-solder paste-coated silicon nitride ceramic sheet, and the sheet is transferred to a high-temperature sintering furnace and sintered at a vacuum degree of 0.01 Pa and a temperature of 900°C for 1 hour to obtain a metal foil-coated silicon nitride ceramic motherboard;
[0043] S4: Coil patterning and surface treatment: The upper and lower surfaces of the metal foil-covered silicon nitride ceramic motherboard are subjected to film lamination, exposure, development, etching, film stripping, and drying to obtain a patterned silicon nitride ceramic motherboard covered with metal coils (wherein the metal coil line width is 1.0 mm, the spacing is 0.8 mm, such as Figure 3 As shown), a silver layer with a thickness of 0.75 μm is plated on the metal coil surface on the upper and lower surfaces to obtain a motherboard A;
[0044] S5: Preparation of a single-layer silicon nitride ceramic metal coil: cutting the motherboard A prepared in step S4 into small pieces according to the designed size by laser, and removing the non-coil area in the middle of the small piece to obtain a single-layer silicon nitride ceramic metal coil;
[0045] S6: Preparation of ceramic isolation sheet: Scribe and punch the ceramic sheet according to the outer dimensions of the single-layer silicon nitride ceramic metal coil and the non-coil area, and open holes at the corresponding positions of the through holes of the single-layer silicon nitride ceramic metal coil to form conductive holes, and obtain the following Figure 4 The ceramic partition shown;
[0046] S7: Lamination and vacuum sintering: A layer of solder paste (7 μm thick) is screen-printed on the upper and lower surfaces of the inner connecting ring and the outer connecting ring of the single-layer silicon nitride ceramic metal coil, dried, and stacked from bottom to top in an alternating manner with the ceramic separator and the single-layer silicon nitride ceramic metal coil, with the ceramic separator on the top, for a total of 21 layers (10 layers for the silicon nitride ceramic metal coil). At the same time, the ceramic separator needs to be filled with copper particles in the via holes in advance (the copper particles are 0.9 mm thick, and the length and width are 1 μm smaller than the via hole size; before the copper particles are filled, their outer surface needs to be wrapped with a layer of solder paste so that the copper particles can be fixed in the via holes). After lamination, it is sintered at 880°C for 40 minutes under a pressure of 0.05 MPa to obtain a high-temperature excitation coil.
[0047] Use a resistance meter to measure the resistance value of the high temperature excitation coil, such as Figure 6 As shown, it is 660.4mΩ.
[0048] in, Figure 2 , Figure 3 and Figure 5 In the figure: ① is the lower metal layer; ② is the silicon nitride ceramic; ③ is the upper metal layer; ④ is the metal coil; ⑤ is the non-coil removal area; ⑥ is the copper particle placement area; ⑦ is the inner connecting circle; ⑧ is the outer connecting circle; ⑨ is the ceramic spacer; ⑩ is the copper particle.
[0049] Conclusion: Based on the AMB process, the metal foil is brazed on the surface of silicon nitride ceramics, and the coil is etched out. After surface treatment, the coil is sintered in an interlaced manner with the magnetic isolation sheet to successfully prepare a high-temperature excitation coil, which has good reliability and service life in an environment of 550℃~600℃.
[0050] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high temperature excitation coil based on the AMB process, characterized in that The following steps are involved: S1: opening holes in silicon nitride ceramics: opening through holes and positioning holes on the silicon nitride ceramic sheet, cleaning and drying, and obtaining a pre-opened silicon nitride ceramic sheet; S2: Through-hole filling and surface screen printing: Fill the through-holes pre-opened by the pre-opened silicon nitride ceramic sheet with solder paste, and screen print a layer of solder paste on the upper and lower surfaces of the pre-opened silicon nitride ceramic sheet, and bake to obtain a pre-coated silicon nitride ceramic sheet with solder paste; S3: Vacuum sintering of metal foil and silicon nitride ceramic: stack a piece of metal foil on the upper and lower surfaces of the silicon nitride ceramic sheet pre-coated with brazing paste, and perform high-temperature vacuum brazing to obtain a metal foil-coated silicon nitride ceramic motherboard; S4: Coil patterning and surface treatment: laminating, exposing, developing, etching, stripping and drying the upper and lower surfaces of the metal foil-covered silicon nitride ceramic motherboard to obtain a patterned silicon nitride ceramic motherboard covered with metal coils, and then coating the metal coil surfaces on the upper and lower surfaces with an anti-oxidation metal layer to obtain a motherboard A; S5: Preparation of a single-layer silicon nitride ceramic metal coil: cutting the motherboard A prepared in step S4 into small pieces according to the designed size by laser, and removing the non-coil area in the middle of the small piece to obtain a single-layer silicon nitride ceramic metal coil; S6: Preparation of ceramic separator: marking and punching the ceramic separator according to the outer dimensions of the single-layer silicon nitride ceramic metal coil and the non-coil area, and opening holes at corresponding positions of the through holes of the single-layer silicon nitride ceramic metal coil to form conductive holes, thereby obtaining a ceramic separator; S7: Lamination and vacuum sintering: Lamination and assembly of the single-layer silicon nitride ceramic metal coil and the ceramic separator from bottom to top, and sintering under pressure to obtain a high-temperature excitation coil.
2. A method for preparing a high temperature excitation coil based on the AMB process according to claim 1, characterized in that: In step S1, the thickness of the silicon nitride ceramic sheet is 0.2-0.4 mm, and the surface roughness of the ceramic is Ra 0.2-0.6 μm; the aperture of the through hole is 0.2-0.8 mm; and the aperture of the positioning hole is 1-5 mm.
3. A method for preparing a high temperature excitation coil based on the AMB process according to claim 1, characterized in that: In step S2, the screen printing thickness of the solder paste is 8-15 μm; the solder paste comprises the following substances, calculated by mass percentage: 8-12% organic carrier, 3-8% active metal powder, and the rest is metal powder.
4. A method for preparing a high temperature excitation coil based on the AMB process according to claim 3, characterized in that: The organic carrier comprises the following substances, calculated by mass: 7.5-8.5 parts of ethyl cellulose, 3-4 parts of hydrogenated castor oil, 1.5-2.5 parts of dioctyl phthalate, 3-4 parts of dibutyl phthalate, 74-76 parts of terpineol, 3.5-4.5 parts of defoamer GP330, and 3.5-4.5 parts of coupling agent KH550.
5. A method for preparing a high temperature excitation coil based on the AMB process according to claim 3, characterized in that: The metal powder comprises silver, copper, nickel and tin in a mass ratio of 60-70:20-30:0-5:0-10; the metal powder is a spherical powder with a particle size of 0.2-1 μm.
6. A method for preparing a high temperature excitation coil based on the AMB process according to claim 1, characterized in that: In step S3, the metal foil includes one of silver foil, copper foil and nickel foil, and has a thickness of 0.1-0.5 mm.
7. A method for preparing a high temperature excitation coil based on the AMB process according to claim 1, characterized in that: In step S4, the wire width of the metal coil is 0.5-3 mm, and the spacing is 0.6-1 mm; the metal in the anti-oxidation metal layer includes one of silver and gold, and the thickness is 0.5-1 μm.
8. A method for preparing a high temperature excitation coil based on the AMB process according to claim 1, characterized in that: During the stacking assembly process, the stacking method is to stack and assemble from bottom to top in an alternating manner with the ceramic separator and the single-layer silicon nitride ceramic metal coil, and the ceramic separator is at the top.
9. A method for preparing a high temperature excitation coil based on the AMB process according to claim 1, characterized in that: The single-layer silicon nitride ceramic metal coil needs to be pre-screened with a layer of solder paste on the upper and lower surfaces of the inner connecting ring and the upper and lower surfaces of the outer connecting ring, and then dried. The solder paste is consistent with that used in step S2; the ceramic separator needs to be pre-filled with copper particles at the conductive holes; the thickness of the copper particles is twice the sum of the thickness of the metal foil and the thickness of the ceramic separator; the length and width of the copper particles are both 0.5 to 3 μm smaller than the size of the conductive holes; before the copper particles are filled, their outer surfaces need to be wrapped with a layer of solder paste so that the copper particles can be fixed at the conductive holes.
10. A method for preparing a high temperature excitation coil based on the AMB process according to claim 1, characterized in that: In step S2, during the drying process, the temperature is 95-105°C and the time is 10-15 minutes; in step S3, during the high-temperature vacuum brazing process, the temperature is 850-950°C, the time is 0.5-1 hour, and the vacuum degree is 0.01Pa.
Citation Information
Patent Citations
Ultrathin heating plate based on etching process and preparation method thereof
CN114710848A
LTCC (Low Temperature Co-Fired Ceramic)-based on-chip transformer structure and manufacturing method
CN117594326A
Active metal brazing ceramic copper-clad plate and preparation method thereof
CN117812816A
Multilayer silicon nitride ceramic substrate based on HTCC and AMB and preparation method
CN118841329A
Wireless charging coil
CN211929252U
Cited By
Micro-channel integrated axial flux motor stator and preparation method thereof
CN120414963A
Micro-channel integrated axial flux motor stator and preparation method thereof
CN120414963B
Multi-layer copper-clad ceramic coil for axial flux motor and preparation method of multi-layer copper-clad ceramic coil
CN120896397A